Of Circuits and Brains: The Origin and Diversification of Neural Architectures - Martinez, Pedro; Sprecher, Simon G. (Frontiers in Ecology and Evolution, 2020)
Nervous systems are complex cellular structures that allow animals to interact with their environment, which includes both the external and the internal milieu. The astonishing diversity of nervous system architectures present in all animal clades has prompted the idea that selective forces must have shaped them over evolutionary time. In most cases, neurons seem to coalesce into specific (centralized) structures that function as “central processing units” (CPU): “brains”. Why did neural systems adopt this physical configuration? When did it first happen? What are the physiological, computational, and/or structural advantages of concentrating many neurons in a specific place within the body? Here we examine the concept of nervous system centralization and factors that might have contributed to the evolutionary success of this centralization strategy. In particular, we suggest a putative scenario for the evolution of neural system centralization that incorporates different strands of evidence. This scenario is based on some premises: 1/ Receptors originated before neurons (sensors before transmitters) and there were deployed in the first organisms in an asymmetric fashion (deposited randomly in the outer layer); 2/ Receptors were segregated in a preferential position in response to an anisotropic environment 3/ Neurons were born in association with this receptors and used to transmit signals distally; 4/ Energetics preferentially selected the localization of neurons, and synapsis, close to the receptors (to minimize wire use, for instance); 5/ The presence of condensed areas of neurons could have stimulated the proliferation of more receptors in the vicinity, increasing the repertoire of signals processed in an specific body domain (i.e. head) plus contributing to amplify the computational power of the neuronal aggregate); 6/ The proliferation of receptors would have induced the proliferation of more neurons in the aggregate, with a further increase in its computational power (hence, diversifying the behavioural repertoire). These last two steps of proliferation and aggregation could have been sustained through a feedback loop, reiterated many times, generating distinct topologies in different lineages. Our main aim in this paper is to examine the brain as both a biological and a physical or computational device.